MY SAY: New world order, G20-style - Abd Razak, Dzulkifli (2009)
So, we have got a "new world order" now, thanks to the 20 "wise" men and women who deemed that it was necessary to craft it over one weekend in London. At a glance, the new order has already been put in place, judging from the triumphant gestures, thrusting economic woes far into the recesses of our minds. For starters, they wined and dined in style, attended to by no less than celebrity chef Jamie Olivier, serving a special G20 menu, some dishes of which were named after the most powerful person on earth. Then, there were the many (if stiff) smiles to fit the photo opportunities. One choreographed "thumbs up" picture was perhaps meant to signal that things are indeed well. Never mind the body language! If one had doubts that the world was on the verge of collapse, the London summit early this month seemed able to distract our attention.